Symptoms and delay times during myocardial infarction in 694 patients with and without diabetes; an explorative cross-sectional study - Hellström Angerud, Karin; Thylén, Ingela; Lawesson, Sofia; Eliasson, Mats; Näslund, Ulf; Brulin, Christine (BMC Cardiovascular Disorders, 2016)
Background: In myocardial infarction (MI) a short pre-hospital delay, prompt diagnosis and timely reperfusion treatment can improve the prognosis. Despite the importance of timely care seeking, many patients with MI symptoms delay seeking medical care. Previous research is inconclusive about differences in symptom presentation and pre-hospital delay between patients with and without diabetes during MI. The aim of this study was to describe symptoms and patient delay during MI in patients with and without diabetes. Methods: Swedish cross-sectional multicentre survey study enrolling MI patients in 5 centres within 24 h from admittance. Results: Chest pain was common in patients both with and without diabetes and did not differ after adjustment for age and sex. Patients with diabetes had higher risk for shoulder pain/discomfort, shortness of breath, and tiredness, but lower risk for cold sweat. The three most common symptoms reported by patients with diabetes were chest pain, pain in arms/hands and tiredness. In patients without diabetes the most common symptoms were chest pain, cold sweat and pain in arms/hands. Median patient delay time was 2 h, 24 min for patients with diabetes and 1 h, 15 min for patients without diabetes (p = 0.024). Conclusion: Chest pain was common both in patients with and without diabetes. There were more similarities than differences in MI symptoms between patients with and without diabetes but patients with diabetes had considerably longer delay. This knowledge is important not only for health care personnel meeting patients with suspected MI, but also for the education of people with diabetes. Funding Agencies|Swedish Heart and Lung Foundation; Swedish Diabetes Foundation; County Councils of Vasterbotten; Heart Foundation of Northern Sweden